(3VhGHW GdSdWI GdJbOjQjI ddbGVi GdLfGFj (B/ s - (3MSf YhV SGde GdWQGhfIs; (3eCehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3jYJHQ GdGKHGJ Gge h GUYH GdehVhYGJ GdJi JhGLg GdbGVi GdLfGFj (B: (3dPG aEf LejY GdGLQGAGJ GdLfGFjI gOagG GdGSGSi gh GKHGJ GdMbjbI HZjI JMbjb GdYOGdI (B: (3hJCJi gPg GdGgejI hGdUYhHI ef chf GdGKHGJ ai GdeSGFd GdLfGFjI GcKQ JYbjOG efg ai GdeSGFd GdeOfjI dCf GdeSGFd GdLfGFjI JQO Ydi hbGFY eGOjI hfaSjI JfJei ddeGVj (B: (3hdjS ai hSY GdeMceI Gf JYGjfgG HfaSgG MGd hbhYgG HNdGa GdhVY ai GdeSGFd GdeOfjI GdJi jchf eMd GdGKHGJ ajgG hbGFY bGfhfjI ef GdjSjQ GKHGJgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B466-473s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdSdWI GdJbOjQjIs; (3GdbGVis; (3GdeSGFd GdLfGFjIs; (3GdJGgjd GdbGfhfi ddbGVis; (3VhGHW JbOjQ GdYbhHgs; (3VhGHW JbOjQ GdJOGHjQ GdGMJQGRjgs; (3JWHjbGJ SdWg GdbGVi GdLfGFi s; (3GdbGfhf GdGQOfi s; (3GdbGfhf GdaQfSi s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs